The impact of digital leadership on innovative behaviour of administrative staff in private universities in China: The mediating role of learning goal orientation - ZhaoFeng, Feng; Mohd Ariffin, Zubaidah (Journal of Islamic, Social, Economics and Development, 2026)
In the context of educational digital transformation, digital leadership serves as a crucial driver for management innovation in private higher education institutions. However, the causal pathways underlying its influence on managerial innovation behaviours remain unclear. Building upon Social Information Processing (SIP) theory, this study constructs a "digital leadership → learning goal orientation → managerial innovation" mediating model. Through empirical analysis of 432 samples from private university administrators using hierarchical regression and Bootstrap methods, the findings reveal: (1) Digital leadership significantly positively influences managerial innovation behaviours; (2) Learning goal orientation acts as a complete mediator between these two factors. The research expands the application scenarios of digital leadership in education, providing theoretical references and practical pathways to stimulate management innovation in private higher education institutions.